Zoometric indices of the Creole sheep in the Chuquibambilla Experimental Centre, Puno, Peru - Ormachea V., Edwin (2020)
The aim of his study was to determine the zoometric indexes of the Creole sheep of the Chuquibambilla Experimental Centre, in Puno, Peru. The study was carried out on a population of 380 female creole sheep older than two years. Various indices were calculated, including ethnological: cephalic index (CI), thoracic index (IT), body index (ICO), pelvic index (IP); milk capacity indices: thoracic metacarpal index (IDT), costal metacarpal index (IDC); meat capacity indexes: relative proportionality index of the thorax (IPRT), transverse pelvic index (IPT), longitudinal pelvic index (IPL), as well as the relative cane thickness (ERC). The results show that the Creole sheep presents characteristics of mesocephalic, brevilinear, convexylline and eumometric animals, with aptitude to develop muscular tissue, easy of calving and adaptation.